(3GdQjGV GdQHGfjI aj GdTYHI GdcJGfjIs - (3CHh GdehGgH LYaQ Hf GOQjS GdMSfj GdcJGfj, GdcJGfj,J (B1323 (3g` s ((3eMeO Hf YHO GdQMje Hf CHj RjO s)
(3ChdgG (B:s
(3hHYO gPG HSJGf XQja jJVef TjFkG ef GdJYQja HTYHJfG GdcJGfjI s
(3BNQgG (B:s
(3hgPG BNQ eG CQOfGg ef gPG GGdeDda GdMajd hGdMeO ddg QH GdYGdejf s
(3Odjd eDQN GdeZQH (B:(3U`(B123s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B122s
(3Odjd eDQN GdeZQH (B- (3U (B123 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B217 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(497 (3c(B) s
Keywords: (3GdJGQjNs